Cytotoxicity of chlorpyrifos on SH-SY5Y human neuroblastoma cell line - Rodríguez Cazar, Lizeth Geomara (2023)
Chlorpyrifos is an acetylcholinesterase inhibitor, which results in acetylcholine accumulation in the synapse. It is an insecticide widely used worldwide and recognized as a moderate human neurotoxin. In 2020, this insecticide was banned throughout the EU but is still commonly used in Ecuador. For that, this work studies the acute toxicity of CPF on human undifferentiated SH-SY5Y cells to assess the impact of pesticides and the mechanism of induced neuronal cell death through studies of oxidative stress detection, MTT assay, and Trypan Blue Test. The counted cells were processed, and a Bar Plot was obtained to analyze the trypan blue data. The data of the MTT assay were analyzed through the dose-response curve. The data obtained from the ROS detection experiments were analyzed through BoxPlots. Finally, a correlation analysis between the experiments was performed. The results of the MTT assay suggested that the cytotoxic effect of CPF on SH-SY5Y cells was statistically significant (p-value < 0.02), as indicated by a dose- and time-dependent decrease in cell viability. These are consistent with the results of the Trypan blue test, indicating that CPF reduces the metabolic activity and viability of SH-SY5Y cells. The highest concentration of CPF (10 µM) caused more than 50 % of cell death. Oxidative stress detection confirmed that CPF exposure increases ROS production in SH-SY5Y cells, which could lead to oxidative damage and neuronal dysfunction. In conclusion, these results suggest that CPF has a neurotoxic effect on SH-SY5Y cells, which could have implications for the development of neurodegenerative diseases.